Criminal Judicial Cooperation from a Central and Eastern European Perspective - Elek, Balázs (The Policies of the European Union from a Central European Perspective, 2022)
Today, the European Union and EU law influence essentially all areas of the law in Member States. Criminal and criminal procedural law are no exception. The European Union can require Member States to criminalize certain defined behaviors, determine the opinion on criminal sanctions that will punish perpetrators, and oblige the states to apply measures in certain areas of criminal law and laws on criminal procedure. As such, the harmonization of substantive and procedural norms in the Member States’ criminal law falls in the EU’s scope of authority.After the accession of the countries of Central and Eastern Europe to the European Union, the harmonization of criminal and criminal procedural law throughout the European Union has been taken to a new level. There were also previously trust-based agreements on criminal co-operation between East and Central European countries, so mutual trust in EU cooperation was not entirely new in these countries. The harmonization has also been facilitated by the fact that there have historically been many similarities between Member States’ legal systems. One of the best examples of this is the habeas corpus principle. The harmonization of criminal procedure rules has already been developed with the countries of East and Central Europe. However, the case law of the European Court of Justice regularly shows that in former Western European countries there is a greater distrust of the legislation of the East-Central European countries and that the new East–Central Member States often approach a legal issue quite differently.Keywords: criminal law, criminal procedural law, principle of mutual recognition, procedural rights.